Alyssa Rusco: capstone - Rusco, Alyssa, artist (Colorado State University. Libraries, 2017)
The artist's statement: When documentation of place and human experience combine, there comes a hybrid observation of the place itself and how it has been consciously altered and used. In some cases, the traces of human interaction are what make the place either more interesting and contemplative, or unsuitable in the eyes of commercial perfection. One's roots do not only grow in places they live, but places they go. After a decade's worth of travelling to Sanibel Island, since I was 11-years-old, I have become akin to the place itself. In this series, I delved into capturing the true likeness of the sites I already knew for what they were. Without glamorizing, I sought to showcase a tropical location, which encompasses the human and the industrial meeting a previously free, natural space. There are rhythms of natural space, altered space, and human-entered space that became undeniable descriptors of how Sanibel has moved me. Past the obvious exotic beauty, Sanibel owns quirks and imperfections that make it more chewable. My kinship has been with the natural and the altered working together in a seemingly perfect landscape. These moments could not have been charmed out of the place itself without the presence of human life bringing its flavor, creating new aspects of the island.
Aspects of the island
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: capstone; photography; photo image making; gallery; senior thesis; senior thesis show; gallery show; island; beach; senior capstone